Pengaruh Budaya Organisasi dan Etika Kerja terhadap Produktivitas Guru SMA Swasta - Muhamad Suhardi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of organizational culture and work ethics on the work productivity of private high school (SMA) teachers in Mataram City in the 2021/2022 academic year. This research was conducted in the odd semester period of the 2021/2022 academic year. The research method used is a survey. The research population is all teachers in private high schools in the city of Mataram. Respondents were selected by simple random sampling technique totaling 125 teachers. The results of the study, based on the analysis obtained data that; 1) The results of a simple correlation analysis obtained a correlation coefficient of 0.575 and a path coefficient value of 0.422. This value indicates that organizational culture has a strong effect on teacher productivity; 2) The results of a simple correlation analysis between work ethics and teacher productivity obtained a correlation coefficient of 0.541 and a path coefficient value of 0.363. In conclusion, based on the results of research and data analysis, it shows that work ethic on teacher productivity has a strong effect. Keywords: Organizational Culture, Work Ethics, Teacher Productivity.